STUDY OF ANTIDIARRHOEAL EFFECT OF AQUEOUS EXTRACT OF YOUNG LEAVES OF COMBRETUM GLUTINOSUM PERR. EX DC - UTHMAN GARBA S; CHABULA MOTA’A S (International Journal of Pharma and Bio Sciences, 2015)
Combretum glutinosum Perr.ex DC of the family Combretaceae is a medicinal plant whose root, stem, bark and leaves are used in the ethno-medical practice of North-Eastern Nigeria for treatment of diverse medical ailments including diarrhoea. However, most of these uses were not validated. The aim of this study is to screen aqueous extract of young leaves of Combretum glutinosum for antidiarrhoeal activity in albino rats. The young leaves of Combretum glutinosum was collected from Hong Local Government area of Adamawa State, Nigeria. The leaves were shade dried and then pulverized into coarse powder which was defatted with petroleum ether and extracted by maceration using cold water. The extract obtained was then used for the antidiarrhoeal screening. The antidiarrhoeal potentials of the aqueous extract of young leaves of Combretum glutinosum was investigated in vivo using castor oil induced diarrhoea and charcoal meal transit time in albino rats. The extract showed dose dependent reduction reduction of diarrhoea castor oil induced diarrhoea with the highest effect observed, with the 600 mg/kg body weight which gave 80.4% protection. The pretreatment of rats with the extract caused a dose dependent and significant (p<0.01) delay in onset of diarrhoea, frequency of stooling and general diarrhoeal score in rats when compared with the negative control. The effect of extract on normal intestinal transit in rats was dose dependent with no statistical significant difference with the control (p>0.05). The results indicate that the aqueous young leaf extract of this plant is well tolerated and relatively safe having significant antidiarrhoeal effect which amply supports its traditional usage.